KEBERLANJUTAN PENGEMBANGAN WISATA PENDIDIKAN BERBASIS KAMPUNG RAMAH ANAK DI DUSUN SABRANGROWO BOROBUDUR MAGELANG - Aryan Torrido (Jurnal Analisa Sosiologi, 2024)
The phenomenon of the increasing number of child-friendly villages (Kampung Ramah Anak, KRA) is directly proportional to the growing number of cases of unsustainability in their management, with some even experiencing stagnation. Various development strategies have been implemented to support KRA initiatives, one of which involves transforming these villages into educational tourism destinations. This approach is designed to enhance public interest in KRA while strengthening local community participation in their management.This phenomenon serves as the scientific rationale for determining the object of study in this research, which focuses on the development of child-friendly village-based educational tourism in Sabrangrowo Hamlet, Borobudur Village, Magelang Regency. The research seeks to answer the question: How sustainable is the development of child-friendly village-based educational tourism in Sabrangrowo Hamlet?. This study employs a qualitative method with a descriptive approach, grounded in three main variables from Jim Ife's community development theory: (1) increasing critical awareness within the community, (2) fostering active participation of the target community, and (3) ensuring the sustainability of development through independent initiatives by the target community.The research findings indicate that the development of child-friendly village-based educational tourism in Sabrangrowo has not progressed, with KRA management showing signs of stagnation. The primary causal factors identified are: (1) efforts to increase critical awareness were primarily focused on youth groups as the main managers, without involving the broader community, and (2) the development program design, which was based on local aspirations, proved less effective because the Sabrangrowo community lacked sufficient knowledge and experience in managing child-friendly village-based educational tourism.The findings emphasize the importance of developing an integrative model of child-friendly village-based educational tourism, supported by intensive mentoring strategies. Such assistance aims to prepare the community to independently manage the program, ensuring sustainability in the long term.